REPRODUCTIVE BIOLOGY OF INVASIVE LIONFISH (PTEROIS SPP.) - Patrick G Gardner (Frontiers in Marine Science, 2015)
Indo-Pacific lionfishes, Pterois volitans (Linnaeus, 1758) and Pterois miles (Bennett, 1828), native to the Pacific and Indian Oceans, respectively, were first observed in the western Atlantic off Florida in 1985. They have since spread and are established throughout the broader Caribbean region. Despite potentially devastating ecological and economic effects, information on key life history characteristics for lionfish in the invaded range is sparse. Objectives of this study were to quantify 1) periodicity in gonad development and spawning, 2) spawning frequency, 3) batch fecundity and 4) female size at maturity for fish from Little Cayman. Calculation of gonadosomatic indices, histological and macroscopic staging of gonads, and counts of hydrated oocytes were applied to determine reproductive characteristics. Higher gonadosomatic indices were recorded for females during periods of stable warm or cool water temperatures indicating that extreme temperatures did not constrain reproduction. Histological and macroscopic staging suggested that male and female lionfish were capable of reproducing year-round. However, higher gonadosomatic indices in females, as expected before spawning, were most pronounced in March/April and August. Based on the proportion of females containing hydrated oocytes, mature lionfish had the potential to spawn every 2–3 d. Ovaries of mature females contained 1800–41945 oocytes that were hydrated in preparation for spawning, with greater numbers of oocytes in larger females. Female lionfish matured at 189–190 mm total length. Parameters estimated in this study can improve outputs from population dynamic models, which will help resource managers design removals and other efforts to control invasive lionfish.